THEORETICAL APPROACHES TO DEFINING SOCIAL STATE - Elena L. Shilkina; Olga B. Podolskaya (Вестник Северо-Кавказского федерального университета, 2022)
The article shows a systematization of the major trends for theoretical explanation of a social state in the European social studies, which is based on an analysis of English literature.